2000
DOI: 10.1074/jbc.m007030200
|View full text |Cite
|
Sign up to set email alerts
|

The MRP2/cMOAT Transporter and Arsenic-Glutathione Complex Formation Are Required for Biliary Excretion of Arsenic

Abstract: Worldwide, millions of people are exposed to arsenic in drinking water that exceeds the World Health Organization standard of 10 g/liter by as much as 50 -300-fold, yet little is known about the molecular basis for arsenic excretion. Here we show that transport of arsenic into bile depends on the MRP2/cMOAT transporter and that glutathione is obligatory for such transport. Using reversed phase liquid chromatography/mass spectrometry, we demonstrate that two arsenic-glutathione complexes not previously identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
209
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(228 citation statements)
references
References 31 publications
13
209
0
1
Order By: Relevance
“…Furthermore, some of the phase I metabolites (e.g., B[a]P-7,8-diol-9,10-epoxide, the activated form of BaP) are suitable substrates for the GSTs (Stegeman and Lech, 1991;Christine Paetzold et al, 2009), and phase I and II metabolism makes many substances more suitable for export via the ABC transporters (Leslie et al, 2005). For example, arsenic-glutathione complex formation is required for the MRP2-mediated transport of arsenic into the bile (Kala et al, 2000), and sulfate conjugation of benzo[a]pyrene generates suitable ABCG2 substrates (Ebert et al, 2005). Therefore, the function of the ABC transporters and biotransformation enzymes could be complementary (Christine Paetzold et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some of the phase I metabolites (e.g., B[a]P-7,8-diol-9,10-epoxide, the activated form of BaP) are suitable substrates for the GSTs (Stegeman and Lech, 1991;Christine Paetzold et al, 2009), and phase I and II metabolism makes many substances more suitable for export via the ABC transporters (Leslie et al, 2005). For example, arsenic-glutathione complex formation is required for the MRP2-mediated transport of arsenic into the bile (Kala et al, 2000), and sulfate conjugation of benzo[a]pyrene generates suitable ABCG2 substrates (Ebert et al, 2005). Therefore, the function of the ABC transporters and biotransformation enzymes could be complementary (Christine Paetzold et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of reduced GSH, arsenite conjugates with three molecules of glutathione to form ATG. The monomethyl metabolite of arsenic conjugates with two equivalents of glutathione to form methylarsenic diglutathione (MADG) [27,39]. The dimethyl metabolite of arsenic conjugates with one equivalent of glutathione to form dimethylarsenic glutathione (DMAG) [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The dimethyl metabolite of arsenic conjugates with one equivalent of glutathione to form dimethylarsenic glutathione (DMAG) [39,40]. Previous study showed that ATG and MADG, but not DMAG, is transported out of hepatocytes via the MRP2/ cMOAT transporter [27]. MRP1 is known to pump out inorganic arsenic as a tri-GSH conjugate at the basolateral membrane [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations